Knockdown of Dinoflagellate Cellulose Synthase CesA1 Resulted in Malformed Intracellular Cellulosic Thecal Plates and Severely Impeded Cyst-to-Swarmer Transition - Chan, Wai Sun; Kwok, Alvin Chun Man; Wong, Joseph Tin Yum (Frontiers in Microbiology, 2019)
Cellulose synthesis (CS) is conducted by membrane-bound cellulose synthase complexes (CSCs), containing cellulose synthases (CesA), that are either arranged in hexagonal structures in higher plants or in linear arrays in most microbial organisms, including dinoflagellates. Dinoflagellates are a major phytoplankton group having linear-type CSCs and internal cellulosic thecal plates (CTPs) in large cortical vesicles. Immunological study suggested CesA1p were cortically localized to the periphery of CTPs. During cyst-to-swarmer transition (TC-S), synchronized peaks of CesA1 transcription, CesA1p expression, cellulose synthesis and CTP formation occurred in respective order, over 12-16 hours, strategically allowing the study of cellulose synthesis regulation and CTP biogenesis. CesA1-knockdown resulted in 40% reduction in CesA1p level and time required for swarmer cells reappearance. CTPs were severely malformed with reduced cellulose content. As CTPs are deposited in internal organelle, the present study demonstrated dinoflagellate CesA1 orthologue was adapted for non-surface deposition; this is different to paradigm of other CesAps which require plasmamembrane for cellulose fibre deposition. This pioneer gene-knockdown study demonstrated the requirement of a gene for dinoflagellate cell wall remodeling and proper TC-S, which are prominent in dinoflagellate life-cycles.